Clinical and genetic predictors of atypical hemolytic uremic syndrome phenotype and outcome - Schaefer, Franz (Kidney international, 2018)
Atypical hemolytic uremic syndrome (aHUS) is a rare, genetic, life-threatening disease. The Global aHUS Registry collects real-world data on the natural history of the disease. Here we characterize end-stage renal disease (ESRD)-free survival, the rate of thrombotic microangiopathy, organ involvement and the genetic background of 851 patients in the registry, prior to eculizumab treatment. A sex-specific difference was apparent according to age at initial disease onset as the ratio of males to females was 1.3:1 for childhood presentation and 1:2 for adult presentation. Complement Factor I and Membrane Cofactor Protein mutations were more common in patients with initial presentation as adults and children, respectively. Initial presentation in childhood significantly predicted ESRD risk (adjusted hazard ratio 0.55 [95% confidence interval 0.41-0.73], whereas sex, race, family history of aHUS, and time from initial presentation to diagnosis, did not. Patients with a Complement Factor H mutation had reduced ESRD-free survival, whereas Membrane Cofactor Protein mutation was associated with longer ESRD-free survival. Additionally extrarenal organ manifestations occur in 19%-38% of patients within six months of initial disease presentation (dependent on organ). Thus, our real-world results provide novel insights regarding phenotypic variables and genotypes on the clinical manifestation and progression of aHUS.
The Global aHUS Registry: Miquel Blasco(Spain), Donata Cresseri (Italy), Galina Generolova (Russia), NicholasWebb (UK), Patricia Hirt-Minkowski (Switzerland), Natalya LvovnaKozlovskaya (Russia), Danny Landau (Israel), Anne-Laure Lapeyraque(Canada), Chantal Loirat (France), Christoph Mache (Austria), MichalMalina (Czech Republic), Leena Martola (Finland), Annick Massart(Belgium), Eric Rondeau (France), Andrew Siedlecki (USA), and LisaSartz (Sweden)
Gesehen am 23.05.2019